Instrument selection for a study of sub cultural differences in Peru - Morales Tristán, Oswaldo; Rees, Gareth (University of California, Institute for Mathematical Behavioral Sciences, 2013)
The interest and appreciation of the differences in cultural values between sub groups within countries is becoming relevant for Latin America due to rising urbanization, social tension and the effects of foreign investments and industrialization. However, few studies have sought to differentiate sub cultural values within Latin American countries, with industry and business academia largely relying on studies that use national measures based on mean scores. This paper, through reviewing the extant cross cultural business literature and Peru’s social history, determines the factors necessary for high quality cross cultural research and the issues will be required to be addressed when selecting or developing a suitable research instrument for sub-cultural studies within a nation state. These issues include defining the sub cultures, instrument sensitivity within a national cultural emic, responsiveness to subject’s response styles and an ability to measure the dimensional constructs appropriately.
Keywords: Cross Cultural Studies; Sub Cultures; Estudios transculturales; Latin America; Subculturas; Peru; América Latina; Perú; Research Methodology; Metodología de la investigación; https://purl.org/pe-repo/ocde/ford#5.02.04